Iconic memory for the gist of natural scenes - Clarke, Jason; Mack, Arien (Consciousness and cognition, 2014)
•Does iconic memory contain the gist or the meaning of multiple natural scenes?•Does iconic memory contain the gist of natural scenes presented in the visual periphery?•We found that iconic memory contains the gist of scenes from different basic-level categories.•We found that iconic memory does not contain the gist of scenes from the same basic-level category.•We found that iconic memory contains the gist of peripherally-presented scenes. Does iconic memory contain the gist of multiple scenes? Three experiments were conducted. In the first, four scenes from different basic-level categories were briefly presented in one of two conditions: a cue or a no-cue condition. The cue condition was designed to provide an index of the contents of iconic memory of the display. Subjects were more sensitive to scene gist in the cue condition than in the no-cue condition. In the second, the scenes came from the same basic-level category. We found no difference in sensitivity between the two conditions. In the third, six scenes from different basic level categories were presented in the visual periphery. Subjects were more sensitive to scene gist in the cue condition. These results suggest that scene gist is contained in iconic memory even in the visual periphery; however, iconic representations are not sufficiently detailed to distinguish between scenes coming from the same category.